Chest Pain with Acute Coronary Syndrome - Alisa Wray, MD (eScholarship Publishing, University of California, 2018)
Audience: This simulation was created for medical students and interns to teach the basics of working up and treatment for a patient with acute coronary syndrome. Introduction: Chest pain is a common presenting chief complaint. It is important for physicians to be able to quickly assess patients with chest pain, develop a differential diagnosis, assess and treat patients for seriously life-threating causes of chest pain. Although acute coronary syndrome and acute myocardial infarctions are less common causes of chest pain it is important for physicians to rapidly recognize an ST segment elevation myocardial infarction (STEMI) and treat accordingly. Objectives: At the end of this case learners should be able to prepare a differential for patients with chest pain, provide appropriate medications for a patient with chest pain, recognize an ST segment elevation MI, and appropriately disposition a patient with acute myocardial infarction (AMI). Method: This simulation can be taught using a low, medium or high-fidelity simulation model or can also be taught using a standardized patient or as an oral boards case. Topics: Chest pain, acute coronary syndrome, acute coronary syndrome (ACS), STEMI